Optimum harvest for sustainable yield of fish live food tubificid worms (Dhaka University Journal of Biological Sciences, 2011)
The Optimum harvest suitable for sustainable yield of tubificid worms without affecting the future yield for a period of 60 days was determined. The media ingredients used to culture the worms were 20% wheat bran, 30% soybean meal, 20% mustard oil cake, 20% cow dung and 10% sand. A harvest level of 50 mg/cm2 (maximum yield; 518.93 ± 14.36 mg/cm2) at ten days interval starting from 30 days of worms' inoculation was found suitable for sustainable yield in the later sampling durations. Results of this study have implications in increasing fish yield by producing reliable and sustainable yield of fish live foods tubificid worms.Key words: Tubificid worms; Live food; Optimum harvest; Sustainable yieldDOI: http://dx.doi.org/10.3329/dujbs.v20i1.8838Dhaka Univ. J. Biol. Sci. 20(1): 57-63, 2011 (January)